(3GdfehPL GdHfGFj ddYdGbGJ GdSHHjI Hjf GdJacjQ GdCNdGbj hGdNOGY GdGcGOjej (B((3GdQbej, hZjQ GdQbej(B) (3hGdYhGed GdNeS GdcHQi ddTNUjI dOi WdGH GdOQGSGJ GdYdjG HGdLGeYI (B/s - (3CSeGA EHQGgje eMehO aQGL,s; (3ShSf GHQGgje TdHi GHh GdYdG s; (3Cejf Ydi SdjeGf s (2022)
(3jgOa GdHMK GdMGdi Edi OQGSI GdYdGbGJ GdEQJHGWjI hfePLI GdYdGbGJ Hjf GdJacjQ GdCNdGbj hGdNOGY GdCcGOjej (B( (3GdQbej, hZjQ GdQbej(B) (3hGdYhGed GdNeS GdcHQi ddTNUjI dOi WdGH GdOQGSGJ GdYdjG(B. (3JchfJ YjfI GdHMK ef (B(302) (3WGdH hWGdHI ef WdGH GdOQGSGJ GdYdjG (B( (3OHdheI(B/ (3eGLSJjQe OcJhQGI(B) (3HGdLGeYGJ GdeUQjI(B. (3hbO JhUd GdHMK Edi HfGA fehPL SHHj jaSQ YdGbGJ GdJCKjQ Hjf GdeJZjQGJ GdKdGKI, hbO CKHJ GdfehPL YOe hLhO JCKjQ eHGTQ OGd EMUGFjkG dcd ef (B( (3GdoYUGHjI hGdEfHSGWjI(B) (3Ydi GdNOGY GdCcGOjej, HjfeG CKHJJ GdfJGFL hLhO JCKjQ SGdH eHGTQOGd EMUGFjkG dcd ef (B( (3GdebHhdjI, hGdVejQ GdMi(B) (3Ydi GdNOGY GdCcGOjej(B. (3ceG CXgQJ GdfJGFL hLhO JCKjQ ehLH eHGTQ OGd EMUGFjkG dcd ef (B( (3GdebHhdjI hGdEfHSGWjI, hGdVejQ GdMj(B) (3Ydi GdJacjQ GdCNdGbi(B.s
The current research aims to study the correlational relationships and model the relationships between moral reasoning and academic dishonesty (digital, and non-digital) and the big five personality traits among postgraduate students. The research sample consisted of (302) postgraduate students (diploma / master's and doctorate) in Egyptian universities. The research has reached the construction of a causal model that explains the effect relationships between the three variables. The model proved that there is no direct, statistically significant effect of each of (neuroticism and extraversion) on academic dishonesty, while the results showed that there is a direct, statistically significant negative effect of each of ( agreeableness and conscientiousness) on academic dishonesty. The results also showed that there is a positive, direct, statistically significant effect of (agreeableness, extraversion, and conscientiousness) on moral reasoning.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2022. s
. (3HHdjhLQGajG(B: (3UaMGJ (B141-193.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdJYdje GdYGdis; (3Yde GdfaS GdJQHhis; (3GdYhGed GdNeS GdcHQj ddTNUjIs -- (3GdNOGY GdCcGOjej(B( (3GdQbej, ZjQ GdQbejs -- (3GdJacjQ GdCNdGbjs